Influences of Environmental and Social Factors on Perceived Bio-Cultural Services and Disservices - Brown, Jeffrey A.; Larson, Kelli L.; Lerman, Susannah B.; Childers, Daniel L.; Andrade, Riley; Bateman, Heather L.; Hall, Sharon J.; Warren, Paige S.; York, Abigail M. (Frontiers in Ecology and Evolution, 2020)
Although the value of urban ecological infrastructure (UEI) is widely recognized, insufficient research has investigated how people perceive the wide variety of UEI. To address this gap, we investigated residents’ perceptions of the coupled value of aesthetic and biological qualities as related to diverse UEI and other environmental and social factors (including personal beliefs and demographics), collectively referred to as bio-cultural services and disservices. We evaluated whether people positively view their neighborhood environments as natural looking while providing diverse plants and wildlife habitat (services), in contrast to negatively perceived disservices that we evaluated as messy looking with weeds and pests (disservices). We analyzed survey data from residents (n=495) in metropolitan Phoenix, Arizona, USA, coupled with environmental variables (UEI and vegetative cover) compiled from diverse sources. We ran three regression models to compare the relative influence of social and environmental factors independently and combined on the perception of bio-cultural services and disservices. Our results demonstrate the influence of social factors, particularly place identity, neighborhood cohesion, and income, on both bio-cultural services and disservices. Additionally, environmental factors such as vegetation cover increased perceptions of bio-cultural services while decreasing perceived disservices. The effects of proximity to UEI were more varied. While proximity to cropland increased perceived bio-cultural disservices, proximity to desert parks reduced disservices. Although UEI can promote biodiversity and human well-being, all UEI are not perceived the same. Our results underscore the added value of considering both the form of UEI and perceptions among people who live nearby when designing and implementing infrastructure to promote bio-cultural services that are both ecologically and socially valued.